Compact and Multiband MIMO Dielectric Resonator Antenna for Automotive LTE Communications - Tzu-Ling Chiu; Laure Huitema; Olivier Pajona; Thierry Monediere (International Journal of Antennas and Propagation)
A compact and multiband dielectric resonator antenna (DRA) designed for LTE automotive solutions is presented in this paper. The proposed MIMO system is located on the vehicle rooftop within a limited space of 120 mm × 70 mm × 65 mm. To cover all the LTE standard frequency bands used around the world, the antenna is matched around 790 MHz–860 MHz, 1700 MHz–2200 MHz, and 2500 MHz–2700 MHz frequency bands with a ∣S11∣ lower than −6 dB while presenting a minimum total efficiency of 50% with a maximum realized gain better than 1 dB on all these frequency bands. The DRA is then mounted and measured on a real vehicle rooftop in order to see its performances in real operation conditions. Finally, to improve both the quality and reliability of the wireless link, two DRAs are placed within a small area to reconfigure their radiation patterns on each frequency band. Measured performances, which are in good agreement with the simulated results, are used to validate if the antenna design is suitable for LTE MIMO systems to be integrated on an automotive. The MIMO system is evaluated using the envelope correlation coefficient (ECC), and the obtained value for the proposed antenna is lower than 0.25.